Abnormal Return dan Trading Volume Activity Sebelum dan Sesudah Rencana Kerja Sama Tesla dengan Indonesia - Rizki, Aditya Kurnia; Utami, Endang Sri (Universitas Teuku Umar, 2023)
The Covid-19 pandemic in 2020 caused a lot of bad news to spread and caused IDX to drop by -37.33% year to date. However, there are stocks that were able to close 2020 positively, one of which is PT Aneka Tambang Tbk (ANTM) because of the sentiment of electric cars. This study aims to analyze the difference of abnormal return and trading volume activity before and after the sentiment of the event of the cooperation plan between Tesla and Indonesia. The type of research is event study with a quantitative approach. The data used is data on the price and transaction volume of ANTM 15 days before and after the sentiment of the cooperation plan between Tesla and Indonesia. The results of the study with paired sample t-test showed that there was a significant difference in abnormal return and trading volume activity of ANTM before and after the sentiment of the cooperation plan between Tesla and Indonesia. Based on the results of the study, the decisions or plans made by regulators will indirectly have an impact on the industry related to an event, including the value of the company reflected in the stock price and more or less investors who make buying and selling transactions on its shares. The results of this study can be used as a reference for investors to be more careful about a decision, plan, or policy change made by the regulator as a consideration in making investment decisions or making stock buying and selling transactions.